Oblast dekretov in vladavina nikogar - Pečarič, Mirko (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2018)
The ever-increasing complexity of regulation of society prevents the classical idea of society's management to be fully apprehended in legal norms. Since this is not possible (any more) also with regulations, an increasing gap may result between the formal determination of rights and obligations and actual implementation. In complex surroundings, accountability cannot be found in one place, which turns it into the rule of nobody. This makes even more important rules, which should be set as clearly as possible. These claims were verified in the case of the Slovenian draft bill on health care and health insurance. The latter demonstrates most of the transfer "weaknesses" of all major powers not only to the executive branch (a government of decrees), but also to the holders of public powers (public institutions outside administration) and their superiors (a government of general rules), in the direction of more and more detailed rules on the expense of individuals to whom the Constitution recognises the fundamental human right to health care. The analysis of the envisaged delegated acts shows that - to avoid the occurrence of litigation and illegal delegation of powers - provided bylaws should be set out more clearly and precisely.
Keywords: authorization to regulate; clause; delegated legislation; emergence; izvršilna klavzula; moč; podzakonski predpisi; pojavnost; power; prenos pooblastil za normiranje